Avaliação da degradação fotoquímica de corante alimentício e lixiviação de corantes têxteis de fibras de algodão expostos a suor sintético por método cromatográficos - Santos, Tuane Cristina dos [UNESP] (2013)
This work investigated the photochemical degradation of the dye tartrazine, widely used in food industry, using spectrophotometric methods and liquid chromatography coupled with diode array (HPLC-DAD) and mass spectrometry (LC-MS/MS) detection. Furthermore, through the Ames test, was studied the mutagenicity of the dye and it`s photodegradation by-products. The photolysis studies were conducted under UV and sunlight, with a more pronounced dye degradation achieved under artificial light in a solution of acidic pH. Total discoloration of a 1x10-5 mol L-1 tartrazine solution was obtained after 30 min of exposure to 125 W UV light, demanding an energy dose of 37.8 J cm-2. The results showed the generation of 5 by-products, derived from the opening of the five-membered ring, identified by LC-MS/MS analysis. The analysis of these data enabled the proposition of a degradation pathway for the dye tartrazine. The Ames test, using Salmonella/microsome, was conducted for the dye at a concentration of 5.34 mg / plate and for the solutions obtained after exposure to UV irradiation, showing that the dye does not possess mutagenic properties for strains TA98 and TA100 of S. typhimurium, with and without exogenous metabolization (S9). In the next step, it was investigated the leaching of dyes Reactive Green 19, Direct Blue 86, Direct Red 81 applied to dye cotton fabrics, when in contact with synthetic sweat. The dyed fabrics were exposed to the synthetic sweat mimicking different pH values, composition, temperature and contact time between the dyed fabric and sweat. The releasing of these dyes in the solutions was monitored using the techniques of UV-Vis spectrophotometry, thin layer chromatography (TLC) and LC-MS/MS. Mass spectra and chromatograms of the Reactive Green 19 standard solution and the samples showed that the dye is extracted from the fabric, by sweat solutions, in all situations tested, and the lower concentrations were found...